2020
DOI: 10.15446/ing.investig.v40n1.80126
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Activated Carbon from Coal for Gold Adsorption in Cyanide Solutions

Abstract: In this work, activated carbons were produced using coal as raw matter from seven Colombian carboniferous zones. Physical activation was performed in two stages: a carbonization stage with Nitrogen at a temperature of 850 °C and a residence time of 2 h, followed by an activation stage using steam at temperatures of 700 and 850 °C with residence times of 1.5 h and 2.5 h. From the pore volume characterization for the adsorption of gold, two activated carbons from Cundinamarca, obtained at 850 °C (1.5 h), 850 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…For the plantain peel, a cylindrical aspect is observed. In contrast, an entanglement structure with porosity is noted for the palm bagasse, typical of lignocellulosic materials (Martínez-Mendoza et al, 2020). This characteristic is extremely beneficial for metal ion transport which increases the adsorption capacity (Pradhan, Arora, and Mahajani, 2018).…”
Section: Adsorbent Characterizationmentioning
confidence: 99%
“…For the plantain peel, a cylindrical aspect is observed. In contrast, an entanglement structure with porosity is noted for the palm bagasse, typical of lignocellulosic materials (Martínez-Mendoza et al, 2020). This characteristic is extremely beneficial for metal ion transport which increases the adsorption capacity (Pradhan, Arora, and Mahajani, 2018).…”
Section: Adsorbent Characterizationmentioning
confidence: 99%
“…At high temperatures, the oxygen containing surface compounds were consumed more easily. As reported by Martinez-Mendoza et al [70], this generates spaces in the structure through which fixed carbon is consumed allowing the widening of the pores. This is because intramolecular dehydration reactions [71] followed by decarboxylation reactions take place in the solid-to-solid conversion pathway [72].…”
Section: Elemental Compositionmentioning
confidence: 75%
“…HTC resulted in an increase in the fixed carbon content and the levels in the hydrochars increased with a rise in the HTC temperature. Martinez-Mendoza et al [70] found that fixed carbon and volatile matter suggest the extent of carbonisation and relate to porosity development in the hydrochars, while an additional activation stage consumes fixed carbon from the char walls, causing them to widen. However, there was no activation process in this present study.…”
Section: Proximate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5: (a) SEM of rice husk; (b) SEM of rice husk char; c) SEM of activated carbon(Hanum et al, 2017) Hidayu, et al (2013). produced activated carbon from oil palm empty fruit bunches and activated with superheated steam at 765 o C for 77 min Martínez-Mendoza, et al (2020). produced activated carbon from Bituminous and subbituminous coal in two stages.…”
mentioning
confidence: 99%